An accelerated-time simulation of baggage traffic in an airport terminal. - Aguilera-Venegas, Gabriel; Galán-García, José Luis; Mérida-Casermeiro, Enrique; Rodríguez-Cielos, Pedro (Elsevier, 2014)
This paper introduces the new ATISBAT model for generating accelerated-time simulations of baggage handling in an airport terminal. The philosophy of this model combines ideas from cellular automaton and neural network theories. The basics of this model was presented at ACA’2012 (in the Nonstandard Applications of Computer Algebra Session). The algorithms involved in the ATISBAT model have been implemented using a Computer Algebra System since some symbolic computations are needed. On the other hand, a Java application that shows the simulation graphically has also been developed. One of the most important characteristics of ATISBAT is its flexibility in two different ways. It allows for the simulation of a wide variety of baggage handling systems. It also allows users to choose from among a great list of random distributions (or even create an “ad hoc” one) to simulate the behavior of the random events within the system. The accelerated-time simulations obtained with ATISBAT, can be used both as an aid during the terminal's design process (in order to optimize the baggage handling network's topology) and also to analyze the impact of any possible proposed changes in an already built baggage handling system. The graphic interface developed produces important visual information about the simulation. This approach is very useful, since the effects of making any change to the system can be immediately visualized.
https://openpolicyfinder.jisc.ac.uk/id/publication/11439
Keywords: Simulación por ordenador; Equipaje - Gestión - Métodos matemáticos; Accelerated-time simulations; Baggage handling design; Baggage traffic simulation; CAS